2011
DOI: 10.4038/cmj.v56i1.2891
|View full text |Cite
|
Sign up to set email alerts
|

Selection of medical students in Sri Lanka: time to re-think criteria?

Abstract: Objective To examine the validity of selected entry level characteristics in relation to the GCE A/L examination as independent predictors of performance of students in medical school.Methods A retrospective, analytical study was done at the Faculty of Medicine, University of Kelaniya. Student characteristics at entry were described by sex, the average z-score, General English grade and attempt at GCE A/L examination, and average mark obtained at the English placement test on registration to medical school.use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2011
2011
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…The article by Hewage et al [13] in the current issue shows the English placement test as a good predictor and furthermore agrees with de Silva et al [8] that A/L attempt (not more than two attempts) is a good predictor. It may not be such a debatable issue that students should not be selected for medicine if they had more than two attempts at A/L and that a test of English language should wholly or partially contribute to the z-score.…”
Section: Tests Of Cognitive Abilitiessupporting
confidence: 86%
See 1 more Smart Citation
“…The article by Hewage et al [13] in the current issue shows the English placement test as a good predictor and furthermore agrees with de Silva et al [8] that A/L attempt (not more than two attempts) is a good predictor. It may not be such a debatable issue that students should not be selected for medicine if they had more than two attempts at A/L and that a test of English language should wholly or partially contribute to the z-score.…”
Section: Tests Of Cognitive Abilitiessupporting
confidence: 86%
“…Although there is limited evidence in Sri Lanka that A/L results predict the student ability throughout their undergraduate medical course [13], the evidence world over suggests that tests of prior cognitive ability (e.g. A/L, MCAT, GPA) predict only the first few years in the medical school [14].…”
Section: Predictors Of Success During the Medical Careermentioning
confidence: 99%
“…Most students (n=117) had obtained an "A" pass at the General English examination, a previously reported predictor of success. (Hewage et al, 2011;de Silva et al, 2006;Ranasinghe et al, 2012) Most reported average or high abilities in the four domains of the English language, although more students reported difficulty in listening comprehension, which would be a disadvantage during lectures. Students who are "low" academic performers are more likely to report poorer competencies in English.…”
Section: English Language Skillsmentioning
confidence: 99%
“…The literature suggests that performance in medical school is affected by varied factors such as entrance examination scores, personality, gender, English language ability, coping skills and availability of academic and social support (Abdulghani et al, 2014;Hewage et al, 2011;De Silva et al, 2006, Ferguson et al, 2002.…”
Section: Introductionmentioning
confidence: 99%
“…A/L) examination in Sinhala or Tamil and apply for admission to study Medicine are not required to show any evidence of proficiency in English. Several studies conducted in Sri Lanka have shown that students with better skills in English at the time of admission perform significantly better in medical school (Mendis & Babapulle 1983, De Silva et al, 2004De Silva et al, 2006a;Mettananda et al, 2006;De Silva et al, 2006b;Hewage et al, 2011). This is despite the fact that almost all medical faculties conduct a three-month intensive course in English on registration of their medical students.…”
Section: Introductionmentioning
confidence: 99%